2018
DOI: 10.1108/md-09-2017-0869
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the intention of smartphone usage by mobile internet users for m-services

Abstract: Purpose This study is exploratory in nature. The purpose of this paper is to examine the intention to use smartphones by mobile users for m-services in a growing market. In fact, it empirically studies the influence of ubiquity and immersion in the virtual context on the perceived value (utilitarian and hedonic) of the mobile user’s experience. Moreover, it is an academic embarkation upon the examination of the effect of perceived value on the intension of using smartphones by mobile users for the m-services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Millennials are considered digital natives (Prensky, 2001) frequently exposed to information and communication technology products and less likely than their elders to exhibit patriotism (Pew, 2011). As millennials have often been used in samples of consumer studies (Ltifi, 2018;Duffett, 2015) and are both current and future major users of smartphone brands, we focus on millennials to understand which constructs of corporate image help develop patriotic brands and how corporate image affects consumers' purchase intentions.…”
Section: Sampling Methods and Data Collectionmentioning
confidence: 99%
“…Millennials are considered digital natives (Prensky, 2001) frequently exposed to information and communication technology products and less likely than their elders to exhibit patriotism (Pew, 2011). As millennials have often been used in samples of consumer studies (Ltifi, 2018;Duffett, 2015) and are both current and future major users of smartphone brands, we focus on millennials to understand which constructs of corporate image help develop patriotic brands and how corporate image affects consumers' purchase intentions.…”
Section: Sampling Methods and Data Collectionmentioning
confidence: 99%
“…Although younger generations have often been used as the sample source in consumer studies of ICT products or services (Duffett, 2015;Ltifi, 2018), ethical consumption (Bucic et al, 2012) and ethnocentrism (Jin et al, 2015), it is a research limitation of this study, as the sample only consists of college students from one university in Taiwan. Hence, the sample is not sufficiently representative.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…[20]. Previous research has found that hedonic value has a positive effect on customer intention [21]- [23], [25], [28]. Thus: H5: Hedonic value has a positive effect on the intention to adopt…”
Section: Hedonic Valuementioning
confidence: 92%